2010
DOI: 10.1063/1.3454243
|View full text |Cite
|
Sign up to set email alerts
|

Charge-transfer absorption band in Zn1−xMxO (M: Co, Mn) investigated by means of photoconductivity, Ga doping, and optical measurements under pressure

Abstract: The nature of the charge-transfer absorption band in undoped and Ga-doped Zn1−xMxO (M: Co, Mn) thin films is investigated by means of photoconductivity and optical absorption measurements under pressure. Internal transitions in the crystal field split Co 3d shell do not contribute to the photoconductivity spectrum and have very low pressure coefficient. Broad absorption bands at photon energies just below the band gap in both ZnMnO and ZnCoO clearly contribute to the photoconductivity spectra, indicating that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 33 publications
1
11
0
1
Order By: Relevance
“…In the absorption measurements, only one ionization channel is seen at energies just below the band gap [2,4,6,9,10]. Based on our results, we assign this transition to t 2↑ → CBM, i.e.…”
Section: Comparison With Experimentsmentioning
confidence: 61%
“…In the absorption measurements, only one ionization channel is seen at energies just below the band gap [2,4,6,9,10]. Based on our results, we assign this transition to t 2↑ → CBM, i.e.…”
Section: Comparison With Experimentsmentioning
confidence: 61%
“…Diluted magnetic semiconductors (DMS) have been recently intensively studied for spintronic applications (Bonanni and Dietl, 2010;Ueda et al, 2001) and ZnCoO focuses a great part of attention here (Khare et al, 2006;Assadi et al, 2009;De Carvalho et al, 2010;Zhang et al, 2009;Gilliland et al, 2010). This is possible because high cobalt concentration in ZnO is expected due to the nearly identical Co 2 þ and Zn 2 þ ionic radii.…”
Section: Introductionmentioning
confidence: 98%
“…24,25 In semiconductors, these are generally band-to-band transitions, but may also include mid-gap impurity photoionization transitions. 28 In some studies, photo-thermal ionization has been suggested, 18,19,22 and in others the 4 T 1 (P) absorption band does not produce any photoconductivity signal, 23 as might have been expected for a localized d-d excitation. The precise locations of the Co 2+ ionization thresholds relative to the ZnO band edges thus remain poorly defined, although these relationships are of central importance not just to photoconductivity but also to the magnetic properties of this same material.…”
Section: Introductionmentioning
confidence: 99%
“…10,11,[16][17][18][19][20][21][22][23] This observation is unusual because photoconductivity selectively probes the excited states of a material that generate mobile charge carriers, i.e., a photocurrent. 24,25 In semiconductors, these are generally band-to-band transitions, but may also include mid-gap impurity photoionization transitions.…”
Section: Introductionmentioning
confidence: 99%